2012
DOI: 10.1111/j.1600-0633.2012.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of gape‐limitation in intraguild predation between endangered Mohave tui chub and non‐native western mosquitofish

Abstract: Intraguild predation (IGP) is a mechanism that may facilitate the co-existence of native species with non-native invasive species. We conducted laboratory predation trials to assess the role of predator gape-limitation in the context of IGP between the endangered Mohave tui chub (Siphateles bicolor mohavensis) and invasive western mosquitofish (Gambusia affinis). Larval tui chubs had significantly lower (v 2 = 74.74; P < 0.001) survival in the presence of female mosquitofish (10.0%) than in the presence of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Relatively low male survival is also consistent with the gape‐size limitation hypothesis as male mosquitofish are much smaller than females. Elsewhere, we have reported the results of laboratory predation trials and vulnerability modelling that also showed evidence for gape‐size limitation in this study system (Henkanaththegedara & Stockwell ). Additionally, in a more food‐limited natural environment, the effects of predation might be even more pronounced as both species would have more motivation to be piscivorous.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Relatively low male survival is also consistent with the gape‐size limitation hypothesis as male mosquitofish are much smaller than females. Elsewhere, we have reported the results of laboratory predation trials and vulnerability modelling that also showed evidence for gape‐size limitation in this study system (Henkanaththegedara & Stockwell ). Additionally, in a more food‐limited natural environment, the effects of predation might be even more pronounced as both species would have more motivation to be piscivorous.…”
Section: Discussionmentioning
confidence: 63%
“…Reduced tui chub larval production was presumably due to mosquitofish predation on tui chub eggs and larvae, rather than competition, because food was provided. Further, it is noteworthy that mosquitofish preyed on tui chub larvae during laboratory trials (Henkanaththegedara & Stockwell ). Other studies have reported mosquitofish predation as the primary mechanism of mosquitofish impact on native fishes (Belk & Lydeard ; Mills, Rader & Belk ; Rogowski & Stockwell ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations